Avatars using computer/smartphone mediated communication and social networking in prevention of sexually transmitted diseases - Gabarron, Elia; Serrano, Jose Artur F S Vale; Wynn, Rolf; Armayones Ruiz, Manuel (BMC Medical Informatics and Decision Making, 2012)
Sexually transmitted diseases (STDs), especially the Chlamydia trachomatis bacterial infection, a common cause of infertility, are highly prevalent in developed countries, and a worrying problem in North Norway, where the incidence of chlamydia twice the Norwegian average. Seventy percent of reported chlamydia cases are found in people below 25 years of age, and although its spread could be controlled with proper prevention, young people are more aware of the risks of unwanted pregnancy than their risk of acquiring a STD. Information and Communication Technologies, including, the Internet, social media and/or smartphones, should be valued for sexual health promotion for their potential to engage young audiences. And in these media, avatars guarantee anonymity to users when handling sensitive information. The main objective of this project is to achieve that North Norwegian youngsters become more aware of STDs through the use of popular technologies among young people.